Is it Time to Reassess the Focal Role of Core PCE Inflation in Assessing the Trend in PCE Inflation? - Verbrugge, Randal (2022)
“Core” PCE inflation—that is, inflation in PCE-ex-food-and-energy—is widely used as an estimate of trend inflation. But it is long overdue for replacement. The original rationale of core inflation was to remove volatile items with transitory shocks. But aside from gasoline, the list of excluded items is far from optimal. Core inflation also su?ers from other severe deficiencies, common to all exclusion indexes. Excluded items often have persistent trends; thus excluding them imparts a significant time-varying bias. Items that are not excluded can experience high volatility, and will cause exclusion indexes to depart notably from trend inflation—as core PCE has done at crucial moments. Two other prominent trend inflation measures, trimmed mean PCE inflation and median PCE inflation, gracefully address these issues (though neither is perfect). A wide variety of evidence comparing these three trend measures is provided. The findings indicate that, for a variety of considerations that are relevant for both trend inflation estimation and for monetary policy deliberations and communication, either trimmed mean PCE inflation or median PCE inflation are superior measures.